Common and personal target genes of the micronutrient vitamin D in primary immune cells from human peripheral blood - Hanel, Andrea (Sci Rep, 2020)
Vitamin D is essential for the function of the immune system. In this study, we treated peripheral blood mononuclear cells (PBMCs) of healthy adults with the biologically active form of vitamin D(3), 1α,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) using two different approaches: single repeats with PBMCs obtained from a cohort of 12 individuals and personalized analysis based on triplicates of five study participants. This identified 877 (cohort approach) and 3951 (personalized approach) genes that significantly (p < 0.05) changed their expression 24 h after 1,25(OH)(2)D(3) stimulation. From these, 333 and 1232 were classified as supertargets, a third of which were identified as novel. Individuals differed largely in their vitamin D response not only by the magnitude of expression change but also by their personal selection of (super)target genes. Functional analysis of the target genes suggested the overarching role of vitamin D in the regulation of metabolism, proliferation and differentiation, but in particular in the control of functions mediated by the innate and adaptive immune system, such as responses to infectious diseases and chronic inflammatory disorders. In conclusion, immune cells are an important target of vitamin D and common genes may serve as biomarkers for personal responses to the micronutrient.